Accounting and Management of Natural Resource Consumption Based on Input-Output Method: A Global Bibliometric Analysis - Wang, Siyun; Tang, Xu; Zhang, Baosheng; Wang, Wenhuan (Frontiers in Energy Research, 2021)
Resources and environment management have always been a research hotspot. In the context of sustainable development and environmental governance, scholars and policy makers have been increasing their research efforts on natural resource utilization and its environmental impact. By using the Web of Science Core Collection database, this paper applies the bibliometric method to accomplish a systematic review about studies on accounting and management of natural resource consumption based on input-output method. The results indicate that both in terms of the quantity and quality of academic achievements and international cooperation, China is in high academic position and has made great contributions to the development in this research field. While energy and water resources account for a large proportion of the study objects, more attention is paid on the other kinds of natural resources, such as land, metal, and ocean. International trade is an eternal hot topic in this field. With the continuous progress of Multi-regional Input-Output Model, the importance and feasibility of analysis of sub-national level or region in global supply chain has gradually emerged. Combining Input-output with other methods can obtain more comprehensive and accurate results for scientific decision-making, meanwhile, the uncertainty and limitations inherent in such models clearly needs further attention.